2017
DOI: 10.1002/mds.26953
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive deep brain stimulation controls levodopa‐induced side effects in Parkinsonian patients

Abstract: The potential superior benefits of adaptive deep brain stimulation (aDBS) approaches compared to classical, constantparameters\ud DBS were already proven by scientific evidence from different research groups. aDBS provides better symptoms control in Parkinson’s disease patients by adapting the stimulation parameters to the patient’s clinical state estimated through the analysis of subthalamic neuronal oscillations (ie,\ud local field potentials) in the beta band (13-30 Hz)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(126 citation statements)
references
References 6 publications
(6 reference statements)
3
122
0
1
Order By: Relevance
“…1B, lower green panel). aDBS substantially reduced the dyskinesias in patients on medication 37,38. In addition, the acute impact of aDBS on speech was assessed in 10 PD patients in a further study 28.…”
Section: Applications and Supporting Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…1B, lower green panel). aDBS substantially reduced the dyskinesias in patients on medication 37,38. In addition, the acute impact of aDBS on speech was assessed in 10 PD patients in a further study 28.…”
Section: Applications and Supporting Evidencementioning
confidence: 99%
“…aDBS substantially reduced the dyskinesias in patients on medication. 37,38 In addition, the acute impact of aDBS on speech was assessed in 10 PD patients in a further study. 28 The patients received bilateral aDBS and cDBS, but only cDBS caused an acute deterioration in speech, assessed through the blinded assessment of the speech intelligibility test.…”
Section: Applications and Supporting Evidencementioning
confidence: 99%
“…Although studies have confirmed the efficacy of 'beta-based' aDBS [9][10][11][12][13], and suggested a superior side effect profile compared to continuous, conventional, DBS (cDBS) [14,15], these have been mostly performed in newly implanted patients. Such studies are potentially compromised by the microlesion effect [16], as this confounding factor provides temporary symptom relief, which can mask the true effects of stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…A number of proof‐of‐concept studies using beta‐LFPs to modify aDBS have shown motor improvement, less speech impairment, and less levodopa‐induced dyskinesia compared to cDBS, which suggests that this is a more efficient and effective method of stimulation. Moreover, a recent study demonstrated the feasibility and beneficial effects on motor symptoms of aDBS over the course of 8 hours in akinetic‐rigid PD patients .…”
Section: Adbs Based On Electrophysiological Recordingsmentioning
confidence: 99%
“…Such differentiation of clinical indications underlines the potential of STN-LFP recordings as promising input signals, with the added benefit of not requiring additional implants or equipment compared to cDBS. 17 A number of proof-of-concept studies using beta-LFPs to modify aDBS have shown motor improvement, 6,18 less speech impairment, 19 and less levodopa-induced dyskinesia compared to cDBS, 20 which suggests that this is a more efficient and effective method of stimulation. Moreover, a recent study demonstrated the feasibility and beneficial effects on motor symptoms of aDBS over the course of 8 hours in akinetic-rigid PD patients.…”
Section: Adbs Based On Electrophysiological Recordings Basal Ganglia mentioning
confidence: 99%